2016
DOI: 10.3390/molecules21101292
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Compositions of Immature Wheat Bran, and Its Antioxidant Capacity, Cell Growth Inhibition, and Apoptosis Induction through Tumor Suppressor Gene

Abstract: Abstract:The purpose of this study was to investigate the phytochemical compositions and antioxidant capacity, cell growth inhibition, and apoptosis induction in extracts of immature wheat bran. Immature wheat bran (IWB) was obtained from immature wheat harvested 10 days earlier than mature wheat. The phytochemical compositions of bran extract samples were analyzed by ultra-high performance liquid chromatography. The total ferulic acid (3.09 mg/g) and p-coumaric acid (75 µg/g) in IWB were significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Overexpressed Bax is able to couple with Bcl‐2 competitively to form Bcl‐2/Bax heterodimers, thereby inducing apoptosis. Similar results were observed by Horie et al (Kim, Yoon, & Kim, ), indicating that the extracts of immature wheat bran played the pro‐apoptotic effect by upregulating expression level of Bax and downregulating the Bcl‐XL and Mcl‐1 expressions. It has been demonstrated that the mitochondria apoptosis, represented by the release of Cytochrome‐C from mitochondria, was partially ascribed to the regulation of Bcl‐2 family expressions (Fu et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overexpressed Bax is able to couple with Bcl‐2 competitively to form Bcl‐2/Bax heterodimers, thereby inducing apoptosis. Similar results were observed by Horie et al (Kim, Yoon, & Kim, ), indicating that the extracts of immature wheat bran played the pro‐apoptotic effect by upregulating expression level of Bax and downregulating the Bcl‐XL and Mcl‐1 expressions. It has been demonstrated that the mitochondria apoptosis, represented by the release of Cytochrome‐C from mitochondria, was partially ascribed to the regulation of Bcl‐2 family expressions (Fu et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were observed by Horie et al(Kim, Yoon, & Kim, 2016), indicating that the extracts of immature wheat bran played the pro-apoptotic effect by upregulating expression level of Bax and downregulating the Bcl-XL and Mcl-1 expressions. It has been demonstrated that the mitochondria apoptosis, represented…”
supporting
confidence: 88%
“…123 A significantly positive correlation was observed between ferulic acid, coumaric acid, syringic acid, and ABTS •scavenging capacity, but only coumaric acid was closely related to DPPH • assay value, and no significant correlation was found between phenolic acid compound and ORAC and Fe 2+ chelating capacity. 40 The results of Kim et al 66 showed that ORAC values were correlated with bound ferulic acid (r = 0.815), free p-coumaric acid (r = 0.823), bound p-coumaric acid (r = 0.779), free syringaldehyde (r = 0.713), and bound syringaldehyde (r = 0.781). It has to be mentioned that the individual phenolic acid antioxidant activity tested by standard reference compounds might differ from the actual antioxidant activity of wheat grain extracts.…”
Section: Rancimat (Rac)mentioning
confidence: 97%
“…127 The antioxidant capacity of wheat bran extracts tested by using CAA was found to be 0.63 μmol L -1 quercetin equivalent (QE)/g in the case of mature wheat and 4.59 μmol L -1 QE•g −1 in the case of immature wheat, while the corresponding total ORAC value (the sum of free and bound) was 44 μmol L -1 TE•g −1 and 54 μmol L -1 TE•g −1 , respectively. 66 Comparing the CAA of 10 wheat varieties, wheat bran of the 'SS520' variety exhibited the highest CAA value of 418 μmol GAE•g −1 , while the 'Chesapeake' wheat variety had the lowest value of 51.3 μmol GAE•g −1 . 50 There was no correlation between the CAA value and any other result determined by chemical techniques.…”
Section: Cellular Antioxidant Activity (Caa)mentioning
confidence: 98%
“…Studies have shown an antioxidant role for tumor suppressor molecules: they adjust the expression of some antioxidant genes in response to oxidative stress [ 53 ]. For example, PTEN (phosphatase and tensin homolog deleted on chromosome 10) performs as this, which is a tumor suppressor gene that is often deleted and/or mutated in a lot of human cancers [ 54 ].…”
Section: Pi3k/akt/pten and P53 Signaling Are Involved In Maintenanmentioning
confidence: 99%